3173 A Mouse Model to Study Image-Guided, Radiation-Induced Cardiac Injury and Potential Clinically Targetable Biologic Mediators. (27th March 2019) - Dreyfuss, Alexandra; Verginadis, Ioannis; Shoniyozov, Khayrullo; Bravo, Paco; Feigenberg, Steven; Ky, Bonnie; Koumenis, Constantinos
Abstract : OBJECTIVES/SPECIFIC AIMS: The overall objective of this study is to develop a novel, clinically-relevant, image-guided mouse model for radiation-induced cardiotoxicity, which can be used to gain insight into clinically-targetable, pathophysiologic mechanisms of cardiac injury in thoracic radiotherapy patients. METHODS/STUDY POPULATION: Photon or sham radiation will be administered at differential doses to a defined portion of the heart and/or lungs of C57BL/6 female mice using micro-CT visualization of the heart with Xstrahl's MuriSlice Software applied to the Small Animal Radiation Research Platform (SARRP). Cardiac and lung segments from a subset of mice will be harvested at specific time points for confirmation of radiation targeting, local apoptosis assessment, and evaluation of fibrosis and vascular tissue morphology. Quantitative echocardiography, myocardial 18F-fluorodeoxyglucose positron emission tomography computed tomography (18F-FDG PET/CT), and myocardial perfusion imaging (MPI) with Technicium-99 (Tc-99) sestamibi will be implemented to identify sensitive imaging measures of cardiac injury and asses myocardial mechanics, inflammation, and perfusion deficits, respectively. Concurrently, a multiparametric analysis will be conducted to identify novel, circulating biomarkers of cardiotoxicity. RESULTS/ANTICIPATED RESULTS: We hypothesize that a clinically-relevant mouse model can be generated by the in situ, focal irradiation of a portion of heart and/or lung tissue segments, and can be used to elucidate molecular mechanisms of radiation-induced cardiac damage. We anticipate time-dependent and dose-dependent, focal histopathologic changes in the mouse heart, with cardiac fibrosis development, vascular damage, and cellular apoptosis in irradiated mice. Additionally, we anticipate that our mouse model of focal heart irradiation will reveal radiologic and biochemical changes that can be used to characterize and predict radiation-induced cardiac injury. Specifically, we expect our quantitative echocardiography, FDG-PET, and MPI parameters to identify and characterize cardiac damage that topographically matches histopathological analysis, and expect levels of select biochemical markers to differentially vary with time. DISCUSSION/SIGNIFICANCE OF IMPACT: Our mouse model of radiation-induced cardiotoxicity has the potential to shift current preclinical research paradigms to more closely mimic the radiation plans most commonly administered in clinical practice. The primary technologic innovation to be developed here is the use of the SARRP to deliver image-guided, in situ, focal radiation to a defined portion of the mouse heart. From a conceptual perspective, we propose a novel approach for phenotyping radiation-induced cardiac damage in patients undergoing chest radiation therapy, integrating sensitive radiomic and biochemical markers into a predictive model of cardiotoxicity.